Genome re-seqeunce and analysis of Burkholderia glumae strain AU6208 and evidence of toxoflavin: A potential bacterial toxin. (June 2020) - Hussain, Annam; Shahbaz, Maham; Tariq, Maria; Ibrahim, Muhammad; Hong, Xianxian; Naeem, Faryal; Khalid, Zunera; Raza, Hafiz Muhammad Zeeshan; Bo, Zhu; Bin, Li
Graphical abstract: Highlights: Genome of Burkholderia glumae strain AU6208 was re-sequenced. The genome size of strain AU6208 was revealed higher than previous version. Specialty genes including virulent genes were identified. The toxoflavin genes resourced from strain AU6208 have variation compared to strain BGR1. Proteins structural variations were noted among both strains Abstract: Burkholderia glumae, the primary causative agent of bacterial panicle blight in rice, has been reported as an opportunistic pathogen in patients with chronic infections. This study aimed to re-sequence the clinical isolate B. glumae strain AU6208 and comparatively analyze its genome using B. glumae strain BGR1 from rice plant as the reference. Re-sequencing results revealed that the genome of strain AU6208 comprised 96 contigs corresponding to a 6.1 Mbp genome of the strain AU6208, with 5322 coding sequences and 68.2 % GC content; this is much larger compared to the genome previously sequenced by us and described by Seo et al (2015), which was reported to be 4.1 Mbp comprising >1200 contigs, 4361 coding sequences, and 67.31 % GC content. Moreover, this updated genome shares >80 % identity to the 7.2 Mbp genome of BGR1, which encodes 6491 coding sequences and has 68.3 % GC content. Further computational analysis revealed that the strain AU6208 encodes several bacteriocin biosynthesis genes, antibiotic, as well as virulent genes such as toxoflavin genes, which included 425 specialty genes and 12 toxoflavin genes. Upon further characterization, 12 toxoflavins (ToxA, B, C, D, E, F, G, H, I, J, TofI, and TofR) were found in AU6208 with 70–100 % sequence, family, and domain similarity with that of BGR1. Upon comparison with BGR1, the structural characterizations of selected toxoflavin genes (ToxB, ToxC, ToxG, H, and TofI) revealed variations in 2D and 3D structures such as differences in α-helix, β-sheets, loops, physiological properties of proteins, RMSD values, etc. These variations may play significant role in different mode of action in different hosts thereby indicating that in addition to their respective hosts, toxoflavins could also contribute to exploit other hosts across the kingdom. In addition to understanding the epidemiology of strain AU6208, this updated genomics data will also unfold the pathogenicity of bacteria in diversity of various hosts and anti-virulence.